Interaction of Islamic Religious Education Teachers with Students in the Learning Process - Ningsih, Andi Mariani; Fitria, Fisky (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: the behavior or ethics of students at SMA Negeri 2 Libureng, Bone Regency, which basically students do not comply with the rules that have been implemented at school which results in a lack of ethics owned by students so that various conflicts arise which basically damage the ethics of the students themselves such as lack of discipline, frequent fights between fellow students and the lack of developing the talents possessed by students. Methodology: The research conducted by the author is classified as a qualitative descriptive research carried out in the field (field research), using observation guidelines, interview guidelines, and documentation formats as instruments for collecting data on students and teachers of Islamic Religious Education subjects which are considered to provide reliable data needed. Main Findings: The results of the study show that there is very good interaction between educators and students in the learning process. This can be seen from the various facilities or means that greatly support the formation of the character that is expected of students to become better individuals. Novelty/Originality of this study: Although there is much research on the importance of ethics in teaching and the role of Islamic religious education in shaping students' moral values, there is limited research that has systematically explored the relationship between the ethics of Islamic religious education teachers and student interactions in certain contexts. educational context, especially in Indonesia. Therefore, this study aims to fill this gap in the literature by providing valuable insights into the relationship between Islamic religious education teacher ethics and student interaction in the learning process.